GRANULOMETRIA E MINERALOGIA DE ARGILAS COMO SUBSÍDIO PARA INTERPRETAÇÃO PALEOAMBIENTAL DA SEÇÃO PEDOESTRATIGRÁFICA LAJEADINHO, GUARAPUAVA - PR - GUERREIRO JUNIOR, LUÍS ANGELO (2017)
The present dissertation aims to understand the pedological evolution of the Pedoestratigraphic section Lajeadinho, located in the Bananas River basin, Guarapuava - PR. The evolutionary hypothesis was based on laboratory responses of clay mineralogy, particle size analysis and comparison with data generated by other authors. The place of work consists of sedimentary and soil material, sectioned by a Stone Line (LP). The study area is located in the region of the Third Planalto Paranaense, with basaltic spills of Serra Geral magmatism, predominantly composed of toleitic basalts. The information obtained in the fieldwork in conjunction with the laboratory results, associated with the bibliographical surveys, allowed the establishment of a pedoambiental hypothesis of modeling the pedoestratigraphic section Lajeadinho from 18K to AP Today Although it was not possible to fully understand the evolutionary process The results obtained allow us to establish that the Lajeadinho outcropping was submitted to two distinct pedoambientes. However, despite the studies already carried out in the region, it is believed that it is necessary to deepen the researches that aim not only to identify its paleoenvironment, but also to seek the establishment of a pedological evolutionary chronology for the region.